ROLE OF CLEAN INTERMITTENT SELF CATHETERISATION (CISC) IN THE PREVENTION OF RECURRENT URETHRAL STRICTURES AFTER INTERNAL OPTICAL URETHROTOMY - khan, Sarhad; Khan, Riaz Ahmad; Ullah, Anayat; Haq, Faheem ul; Rahman, Ata ur; Durrani, Sadia Nawaz; Khan, Muhammad Kamran (Journal of Ayub Medical College Abbottabad, 2011)
Background: Urethral stricture is one of the oldest diseases Urethral dilatation Internal optical urethrotomy,were the only treatment. Clean Intermittent Self Catheterisation was introduced by Lapides has greatly decreased the recurrence of stricture. Objectives were to determine the role of Clean Intermittent Self Catheterisation (CISC) in the prevention of recurrence of urethral strictures after Internal Optical Urethrotomy and to study the frequency of any postoperative complications and tolerability for the patients associated with this procedure. Methods: A randomised controlled study conducted in the department of urology and renal transplantation, Institute of Kidney Diseases Hayatabad Medical Complex, Peshawar from June 2007 to June 2010. Total of 60 patients with mean age 48 years (range 20-73) were selected and randomly divided into Treatment Group (30 patients) and Control Group (30 Patients). Eight drop out occurred in the treatment group and four drop out occurred in the controlled group. All the patients were treated with Internal Optical Urethrotomy using Sachse method followed by indwelling catheter for 5 days. The treatment group was then taught to perform Clean Intermittent Self Catheterisation by inserting a Classic Neleton Catheter (No. 16 or 18) twice a day for 1 week, then once a day for another 4 weeks and then once weekly continued for one year. All the patients were followed up regularly at 1 month intervals during the first 6 months and then every 2 months for the next 6 months. Results: Total of 48 patients completed the study, 22 in the treatment group and 26 in the control group. Within the first year, 4 patients (22%) in the treatment group developed urethral stricture. In the control group, 12 patients (46%) developed urethral stricture within the first year, showing a significant difference (p<0.01). In the treatment group four patients developed simple UTIs while in the control group three patients developed UTIs, one with concomitant epididymitis. No other complications were noted up to one year follow up. Conclusion: Clean Intermittent Self Catheterisation is a simple and effective way of reducing stricture recurrence after Internal Optical Urethrotomy and is associated with less morbidity and is cost effective. CISC is an important modality for maintaining the normal urethral calibre. Keywords: Urethral Strictures, Optical Urethrotomy, Clean Intermittent Self Catheterisation, Recurrence, Complications